Work made fun gets done! : easy ways to boost energy, morale, and results - Nelson, Bob; Tamayo, Mario (Oakland, CA : Berrett-Koehler Publishers, Inc., 2021)
According to the employees that work for firms listed in Fortune's "100 Best Companies to Work for in America," the most defining characteristic of these organizations is they are all "fun" places to work. Fun is the secret sauce every business needs to better engage and motivate its employees today. Work Made Fun Gets Done! gives readers simple, practical ideas for instantly bringing fun into their work and workplace. Based on examples from scores of companies like Zoom, Pinterest, Bank of America, Zappos, Honda, Microsoft, and many more, this book provides clear examples of exactly what managers and employees alike can do to lighten the tone in the work environment and allow employees to have more fun at work.
PART 1. Individual Oriented Fun -- PART 2. Leader-Oriented Fun -- PART 3. Team Oriented Fun -- PART 4. Organization Oriented fun.
Keywords: LABOR PRODUCTIVITY; EMPLOYEE MOTIVATION